Nutrition Reinvented: Ai-Powered System For Personalized Dietary Insight (International Journal of Environmental Sciences, 2025)
The AI-Powered Nutrition System is designed to meet the growing need for personalized dietary monitoring by delivering real-time nutritional insights derived from food images. Using advanced technologies such as convolutional neural networks (CNNs), natural language processing (NLP), and computer vision, the system offers a comprehensive approach to dietary analysis. Key features include dish detection, ingredient recognition, and freshness evaluation, enabling users to receive detailed nutritional breakdowns, such as calorie counts, macronutrient compositions, and personalized dietary recommendations tailored to their needs.The system begins by preprocessing food images to optimize input data quality. CNNs are employed for precise dish recognition, ensuring accuracy even with visually complex meals. Ingredient recognition identifies components of the dish, while freshness analysis evaluates the quality of ingredients, providing a holistic view of the food's nutritional value. External APIs like Nutritionix are integrated to retrieve up-to-date nutritional data, ensuring reliability and relevance.With an impressive accuracy of 95% in dish detection, 93% in ingredient recognition, and 90% in freshness analysis, the system demonstrates robust performance across critical features. Its scalability and adaptability make it a promising tool for diverse user groups. Planned future enhancements include multilingual support for global accessibility, integration with wearable devices for real-time health monitoring, and condition-specific dietary planning to cater to users with unique dietary needs. This system sets a strong foundation for transforming dietary habits through innovative, technology-driven solutions.